Electromyographic analysis of knee push up plus variations: what is the influence of the kinetic chain on scapular muscle activity?. Issue 14 (14th September 2009) - Maenhout, A; Van Praet, K; Pizzi, L; Van Herzeele, M; Cools, A
Abstract : Objective: First, to look for appropriate closed kinetic chain exercises to restore intramuscular imbalance between upper trapezius (UT) and serratus anterior (SA) in overhead athletes. Second, to determine the influence of using diagonal pattern muscle recruitment during knee push up plus (KPP) exercises on scapular electromyographic activity. Design: Single group repeated-measures design. Setting: Controlled laboratory study. Participants: Thirty-two physically active individuals in good general health who did not have a history of neck and/or shoulder injury or surgery nor participated in high-level overhead sports or performed upper limb strength training for more than 5 h/week. Interventions: Subjects performed the standard KPP and six variations. Main outcome measurements: Electromyographic activity of the three trapezius parts and the SA. Results: Four exercises with a low UT/SA can be selected for rehabilitation of intramuscular balance: standard KPP, KPP with homolateral leg extension, KPP with a wobble board and homolateral leg extension and one-handed KPP. The use of a wobble board during KPP exercises and performance on one hand has no influence on SA electromyographic activity. Heterolateral leg extension during KPP stimulates lower trapezius activity, whereas homolateral leg extension stimulates SA activity. Conclusions: In case of intramuscular scapular imbalance, some exercises are preferable over others because of their low UT/SA ratio. The use of a kinetic chain approach during KPP exercises influences scapular muscle activity.